Circulating β cell‐specific CD8+ T cells restricted by high‐risk HLA class I molecules show antigen experience in children with and at risk of type 1 diabetes - Yeo, L.; Pujol‐Autonell, I.; Baptista, R.; Eichmann, M.; Kronenberg‐Versteeg, D.; Heck, S.; Dolton, G.; Sewell, A. K.; Härkönen, T.; Mikk, M.‐L.; Toppari, J.; Veijola, R.; et al. (Clinical and experimental immunology, 2020)
Summary In type 1 diabetes (T1D), autoreactive cytotoxic CD8+ T cells are implicated in the destruction of insulin‐producing β cells. The HLA‐B*3906 and HLA‐A*2402 class I genes confer increased risk and promote early disease onset, suggesting that CD8+ T cells that recognize peptides presented by these class I molecules on pancreatic β cells play a pivotal role in the autoimmune response. We examined the frequency and phenotype of circulating preproinsulin (PPI)‐specific and insulin B (InsB)‐specific CD8+ T cells in HLA‐B*3906+ children newly diagnosed with T1D and in high‐risk HLA‐A*2402+ children before the appearance of disease‐specific autoantibodies and before diagnosis of T1D. Antigen‐specific CD8+ T cells were detected using human leucocyte antigen (HLA) class I tetramers and flow cytometry was used to assess memory status. In HLA‐B*3906+ children with T1D, we observed an increase in PPI5–12‐specific transitional memory CD8+ T cells compared to non‐diabetic, age‐ and HLA‐matched subjects. Furthermore, PPI5–12‐specific CD8+ T cells in HLA‐B*3906+ children with T1D showed a significantly more antigen‐experienced phenotype compared to polyclonal CD8+ T cells. In longitudinal samples from high‐risk HLA‐A*2402+ children, the percentage of terminal effector cells within the InsB15–24‐specific CD8+ T cells was increased before diagnosis relative to samples taken before the appearance of autoantibodies. This is the first study, to our knowledge, to report HLA‐B*3906‐restricted autoreactive CD8+ T cells in T1D. Collectively, our results provide evidence that β cell‐reactive CD8+ T cells restricted by disease‐associated HLA class I molecules display an antigen‐experienced phenotype and acquire enhanced effector function during the period leading to clinical diagnosis, implicating these cells in driving disease. In this study, we characterised circulating autoreactive CD8+ T cells in children with type 1 diabetes with HLA-B*3906+ and HLA-A*2402+ genotypes which are associated with increased risk and early onset of disease. In HLA-B*3906+ children with newly diagnosed type 1 diabetes, we observed an increase in PPI5–12‐specific transitional memory CD8+ T cells compared to non‐diabetic, age‐ and HLA‐matched subjects. Furthermore, PPI5–12‐specific CD8+ T cells in HLA‐B*3906+ children with T1D showed a significantly more antigen‐experienced phenotype compared to polyclonal CD8+ T cells. Further, in longitudinal samples from high-risk HLA-A*2402+ children, the percentage of terminal effector cells within the InsB15–24‐specific CD8+ T cell population was increased before diagnosis relative to samples taken before the appearance of autoantibodies.